Analisis Hukum dalam Kasus Pemerkosaan Berdasarkan Berita Acara Pemeriksaan (BAP) No: Lp/03/1/2022/Ntt/ Reskrim Manggarai Timur - Samara, Finsensius; Fattu, Macho; Bere, Elisabeth Candra; Purdita, Benediktus Reza; Henuk, Marsya Ananda Olivia; Wacu, Jiando Andu (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the crime of rape as reflected in the Berita Acara Pemeriksaan (BAP) in a rape case that occurred in East Manggarai Regency. This case demonstrates intentional sexual violence, accompanied by threats and physical violence, resulting in profound physical suffering and psychological trauma for the victim. Using a normative juridical approach, examining the victim's testimony and applicable criminal law provisions, this study examines the elements of rape as stipulated in Article 285 of Kitab Undang-Undang Hukum Pidana (KUHP). The results indicate that the perpetrator's actions met the elements of coercion, violence, and intercourse without the victim's consent. Furthermore, this case illustrates the weakness of initial protection for victims when amicable resolution fails to provide justice and instead opens up opportunities for recurrence. Therefore, this study emphasizes the importance of firm law enforcement, recovery-oriented victim protection, and the role of law enforcement officials in guaranteeing the rights of victims of sexual violence.